Ultrasonography of the Hand in Rheumatology (Springer International Publishing, 2018)
This book is an essential guide for rheumatologists using ultrasound to study musculoskeletal structures and diagnose rheumatic diseases of the hand. A fundamental understanding of anatomy is key to identifying and interpreting pathological findings on imaging. This book provides comprehensive knowledge about both gross anatomy and, more importantly, comparative imaging anatomy, as depicted by ultrasound, X-ray, and MRI of the hand. This foundation enables clinicians to readily identify pathologic findings and thus improve diagnostic skills. The authors also offer step-by-step guidelines for using ultrasound, with comprehensive descriptions about body and transducer position, sonographic terminology, and anatomical landmarks in different planes of the hand. This book is an indispensable reference for rheumatologists and rheumatology residents using musculoskeletal ultrasound in clinical practice.